Optimizing Gravity Forward Modeling through OpenMP Parallel Approach: A Case Study in Bawean Island - Indra Gunawan; Susanti Alawiyah (Telkom University, 2025)
This study investigates the optimization of Gravity Forward Modeling (GFM) by implementing an OpenMP parallel computing approach, focusing on the synthetic model and topography of Bawean Island. The research addresses computational limitations in traditional GFM by utilizing parallel processing techniques to enhance efficiency and resolution. By modeling subterranean layers with rectangular prisms and using the Okabe equation for calculations, the study significantly improves computational speed and resource management. The practical application on Bawean Island includes a strategic distribution of observation stations to facilitate Bouguer Anomaly (BA) computations, providing a clearer understanding of subsurface density anomalies. Notably, the study demonstrates a 600% increase in efficiency for the synthetic case when OpenMP with 8 threads is applied to the utilized architecture. For the field model, computations spanning 400 square kilometers on Bawean Island, encompassing over 1.3 billion GFM calculations, are completed in just 143 seconds. Additionally, the gravity terrain values on Bawean Island exhibit a range of up to 65 mGal, which closely correlates with the high-resolution topographic map. These findings highlight the considerable advantages of parallel computing in enhancing the efficiency and feasibility of complex geophysical modeling tasks, offering substantial improvements for large-scale geophysical exploration.